The interaction between physical exercise and nanoscience: a systematic review - Ramos, Darcieli Lima; Rech, Virginia Cielo (Disciplinarum Scientia | Naturais e Tecnológicas, 2020)
While the potential of nanoparticles in medicine has been widely explored, what do we know about their association with physical exercises? The aim of this study is to conduct a systematic review assessing the potential interaction between physical exercise and nanoparticles. This review was done in June 2019 on the Scielo, Medline, Pubmed, and Scopus databases, using the descriptors “exercise” and “nanoparticles.” No articles were found on the Scielo database. The search on Medline, Pubmed and Scopus returned 38, 98 and 168 references, respectively. After assessing the title, abstract and descriptors, duplicate references were excluded as well as studies that did not have the exercise or nanoparticles as variables. After screening, 28 studies were included in this review. Our results show that there is a positive correlation between nanoparticles, specially those with antioxidant properties, and physical exercise, in different studies conducted around the world. However, there is little bibliography on the subject to affirm that a nanostructure is more efficient than the other. In addition, further studies should be conducted on physical exercise and nanoparticles.